An efficient tool for genetic experiments: agarose gel image analysis - Adiga, P; Flint, J (2003)
Repeatability of many genetic analysis experiments can be improved by the application of signal processing and image-processing tools. Most of the experiments in genetics result in some sort of digital signal or image patterns that are subjectively analyzed by the geneticists. This paper presents an example project where image-processing techniques are applied for automation of most of the routine processes of agarose gel image analysis. Result of applying this program has shown that the time taken for the analysis has been reduced by about 70% and the result is reproducible. © 2003 Pattern Recognition Society. Published by Elsevier Ltd. All rights reserved.